STUDY OF PHASE TRANSFORMATIONS IN FERROELECTRICS BASED ON CALCIUM TITANATE - Kozlovskiy, A.L.; Zdorovets, M.V. (KU Publ., 2021)
The aim of this work is to study phase transformations kinetics in ferroelectrics based on calcium titanate. The relevance of this study is in the assessment of new methods for obtaining complex phase composition ferroelectrics, which have the potential for application in microelectronics, photocatalysis, and power engineering. The methods of scanning electron microscopy and X-ray diffraction were used as the main methods of analysis. Analysis of morphological features made it possible to establish the kinetics of changes not only in grain sizes, but also in their geometry. During the studies of phase transformations, the following dependence of the TiO2 – anatase/CaTi2O4 → TiO2– anatase /CaTi2O4/CaTiO3 → CaTiO3/TiO2 – rutile type was established depending on the annealing temperature. At the same time, at a temperature of 1000°C, a stable structure of ceramic with a perovskite-like structure of the CaTiO3 type and a high structural ordering degree (more than 92%) is formed.
Keywords: calcium titanate; phase transformations; perovskites; ferroelectrics; crystallinity degree